(untitled) (Stavební obzor - Civil Engineering Journal, 2018)
For the innovation of building materials, a new high-performance Steel Fiber Reinforced Lightweight-Aggregate Concrete (SFRLAC) made of 100% fine and coarse expanded shales has been developed. In view of the importance of reliable bond properties between deformed rebar and this new SFRLAC, the experimental study of 39 specimens was conducted by using the modified pull-out test method with the evaluation of different slips at loading-end and free-end. In which the influencing factors were considered as the volume fraction of steel fiber, the water-cement ratio, the rebar diameter, the bond length of rebar, the strength of coarse expanded shales and the fine expanded shale replaced by manufactured sand. The complete bond stress-slip curves were measured, the bond failure modes of specimens were observed. Based on the bond mechanism of adhesion, friction and bearing action of deformed rebar in SFRLAC, the bond performance characterized by the bond strength and peak-slip, the differential of bond slip between loading-end and free-end, the bond sustainability in descending portion and the bond failure mode observed are analyzed. The recommendations are proposed for the design of SFRLAC structures related to the bond performance.